2012
DOI: 10.1371/journal.pone.0042029
|View full text |Cite
|
Sign up to set email alerts
|

Stavudine Toxicity in Adult Longer-Term ART Patients in Blantyre, Malawi

Abstract: BackgroundStavudine is an effective and inexpensive antiretroviral drug, but no longer recommended by WHO for first-line antiretroviral regimens in resource-limited settings due to toxicity concerns. Because of the high cost of alternative drugs, it has not been feasible to replace stavudine in most adults in the Malawi ART programme. We aimed to provide policy makers with a detailed picture of stavudine toxicities in Malawians on longer-term ART, in order to facilitate prioritization of stavudine replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…Patients using a combination of zidovudine in this study of patients were anemic when using zidovudine-containing therapy, and as many as 15% of the patients had to substitute therapy due to severe anemia. The results of this study were in line with the results of a study conducted by Parkes-Ratanshi et al (2016) that showed the risk of anemia in patients taking zidovudine was 2.7 times greater than that of patients taking a tenofovir combination [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients using a combination of zidovudine in this study of patients were anemic when using zidovudine-containing therapy, and as many as 15% of the patients had to substitute therapy due to severe anemia. The results of this study were in line with the results of a study conducted by Parkes-Ratanshi et al (2016) that showed the risk of anemia in patients taking zidovudine was 2.7 times greater than that of patients taking a tenofovir combination [5].…”
Section: Discussionsupporting
confidence: 91%
“…Stavudine was replaced by tenofovir, which was formerly a second-line therapy [5]. Tenofovir has shown fewer side effects compared to either stavudine or zidovudine [6].…”
Section: Introductionmentioning
confidence: 99%
“…35 Pancreatitis has been predominantly associated with the usage of nucleoside reverse transcriptase inhibitors (NRTIs) such as didanosine and stavudine. 36 Being used widely and frequently, NSAIDs are often associated with ADEs. 37 The main safety concerns while using NSAIDs are gastrointestinal, renal, cardiovascular, hematologic effects, hepatic and allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…It represents a management problem because of its diverse modes of expression, multiplicity of causes and the high mortality rate. [4] Historically, this has been predominantly associated with the usage of nucleoside reverse transcriptase inhibitors (NRTIs) such as didanosine and stavudine [5,6], release of opportunistic agents (cytomegalovirus, cryptosporidiosis, Mycobacterium tuberculosis) or Kaposi disease. The advent of protease inhibitors in the late 1990s enabled a clear regression of incidence of these diseases [7].…”
Section: Introductionmentioning
confidence: 99%